Standardization of propagation method in avocado (Persea americana) (Current Horticulture, 2024)
The experiment was conducted to standardize the method and time of propagation of avocado (Persea americana Mill) through vegetative means at CHES, ICAR-IIHR, Chettalli, during 2012-13. There were four methods of multiplication i.e. veneer grafting, cleft grafting, T-budding and patch budding, performed throughout the year. After 90 days of grafting, mean success was highest in cleft grafting (32.5%), followed by veneer grafting (8.3%), T-budding (7.5%) and patching budding (5.8%). There was highest mean success during September (32.5%), followed by 22.5 per cent during March and August 2012. Among different combinations of months and propagation methods, highest success (70%) was recorded in cleft grafting performed during September 2012. This was closely followed by same method done during March 2012 (60%). The success in cleft grafting was higher than other three methods throughout 2012-13. The growth of the scion was higher in grafting methods than budding methods. The transplantable seedlings after one year were highest (60%) in cleft grafting done September 2012. Thus, cleft grafting during September and March was found most suitable for vegetative propagation of avocado under humid tropical conditions.
Keywords: Avocado; Budding; Grafting; Vegetative Propagation